Application of inpainting technique for reconstruction of partially detected curvilient features derived from the process of extraction of cartographic features - Figueira, A. [UNESP]; Da Silva, E. [UNESP] (IOP Publishing, 2020)
Extraction processes of cartographic features from digital images have been of great importance in the area of Cartography, however, the results obtained by these techniques usually have partially detected features, culminating in loss of quality of the extraction process. Thus, this work shows how to improve the quality of the extraction process, by employing an inpainting based technique proposed by Deng L-J et al. The use of this algorithm may contribute greatly to increasing quality of the process of extraction of curvilinear cartographic features partially detected in digital images and can be used in the area of cartography, supporting processes to update cartographic products.